2013
DOI: 10.3945/ajcn.113.058743
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota after gastric bypass in human obesity: increased richness and associations of bacterial genera with adipose tissue genes

Abstract: Background: Roux-en-Y gastric bypass (RYGB) surgery is one of the most efficient procedures for treating morbid obesity and results in weight-loss and improvements in metabolism and inflammation. Objective: We examined the impact of RYGB on modifications of gut microbiota and its potential associations with changes in gene expression in white adipose tissue (WAT). Design: Gut microbiota were profiled from fecal samples by using pyrosequencing in morbidly obese individuals, explored before (0 mo), 3 mo after, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
260
5
12

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(316 citation statements)
references
References 44 publications
39
260
5
12
Order By: Relevance
“…A recent review of bariatric surgery in adolescent patients found little difference in weight reduction when Roux en Y was compared with sleeve gastrectomy [25] . The patients who had the Roux en Y procedure were the heaviest at the start with a mean BMI of 54 (52)(53)(54)(55), whereas the sleeve gastrectomy subjects had a mean BMI of 50 (48)(49)(50)(51)(52). The percent change was 28 for the Roux en Y as compared to 26 for the sleeve gastrectomy operation.…”
Section: Bariatric Surgery and Type 2 Diabetesmentioning
confidence: 84%
See 1 more Smart Citation
“…A recent review of bariatric surgery in adolescent patients found little difference in weight reduction when Roux en Y was compared with sleeve gastrectomy [25] . The patients who had the Roux en Y procedure were the heaviest at the start with a mean BMI of 54 (52)(53)(54)(55), whereas the sleeve gastrectomy subjects had a mean BMI of 50 (48)(49)(50)(51)(52). The percent change was 28 for the Roux en Y as compared to 26 for the sleeve gastrectomy operation.…”
Section: Bariatric Surgery and Type 2 Diabetesmentioning
confidence: 84%
“…The authors suggest that the changes are perhaps due to the differences in diet after the operation or very low calorie diet of the non-operated subjects. Kong et al [52] examined gut microbiota after Roux en Y surgery, and found increased microbiota, 37% due to proteobacteria. They also found an increase in Bacteroides.…”
Section: Microbiotamentioning
confidence: 99%
“…These ''Western'' diseases are increasing in prevalence, and manipulating the gut microbiota is an attractive therapeutic approach in their management. Strategies for combating obesity and related conditions that involve manipulating the gut microbiota include bariatric surgery [78,79], microbial transplantation [80,81] and probiotics [82].…”
Section: The Changing Phenotype Of Ibdmentioning
confidence: 99%
“…The gut microbiome changes after gastric bypass surgery in humans, [66][67][68] rats 69 and mice, 70 and a recent transplant study in mice suggests that the changes in gut microbiome are responsible for at least some effects on body weight. 70 The signaling pathways leading from the microbiota in the intestinal lumen to reduced body weight are not known (Figure 3).…”
Section: Role Of Microbiota-host Interactionsmentioning
confidence: 99%